The Concept Of Implementing Active Learning Strategies In Islamic Religious Education Learning - Firmansyah; Irja Putra Pratama; Mukti Ali; Miftahul Husni; Siti Fatimah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2024)
This study aims to elaborate the concept of active learning strategy implementation in Islamic religious education learning, which will be divided into three main discussions, including: 1) the definition of active learning strategies; 2) components and supporting factors of active learning strategies; 3) various methods in active learning strategies; and 4) implementation of active learning strategies in Islamic religious education learning. This research uses a library research approach, to analyze the concept of implementing active learning strategies in Islamic religious education learning in Mel Silberman's book, Active Learning: 101 Strategies To Teach Any Subject. Data collection was carried out using documentation techniques, which were then analyzed inductively. The results showed that active learning strategy is a learning approach that invites students to engage directly through real experiences, empowering them to learn actively in various ways and strategies. Components such as experience, interaction, communication, and reflection are key in implementing active learning strategies. Factors such as teacher attitude and behavior play an important role in supporting active learning. The book